Climate change impacts on rice production in Japan: A Cobb-Douglas and panel data analysis - Caixia Li (Ecological Indicators, 2023)
This study provides an overview of the most important factors of climate change impacting on rice production and the methods to measure the degree of the climate change affect to agricultural production by prefectures in Japan. Cobb-Douglas production function combining with panel data analysis is applied to describe the relationship between the productive factors and production. Due to analyzing the impact of climate change to rice production further, we create the panel data for 7 regions (Tohoku includes Hokkaido) by 46 prefectures. In addition, we set rice production as dependent variable, and labor, temperature, precipitation, duration of sunshine, wind speed and TE (technical progress) as controlled variables. The main purpose of this study is to analyze which climate change factor impacts the most on rice production, whether the impact is positive or not. We found that there is an invert U-shape existed between temperature and rice production, and precipitation and wind speed negatively affected rice production for whole country. In addition, sunshine duration affects rice production positively. For regions, the results are quite different because of different latitude or other impacting factors omitted. We concluded that the additional climatic variable wind speed negatively affected to rice production in most prefectures. In addition, temperature positively affects rice production except for Kyushu region. In order to adapt the wind speed strong suddenly, the selection of rice seeds is important in the rice growing season. Choosing the rice seeds that are anti-high-speed wind is extremely important.